Study on support characteristic curve of concrete-filled steel tubular arch in underground support. (October 2020) - Lu, Wei; Sun, Huibin
Abstract: Concrete filled steel tubular (CFST) arch has broad application prospects as a high-strength support form in underground excavations, especially in weak and broken surrounding rock. However, the structural design of CFST arch in underground excavation still relies on experience-based method and lack of quantitative mechanical analysis. This paper presents a detailed analysis on the mechanical behavior of CFST arch and proposed an analytical model to construct support characteristic curves (SCC) according to convergence-confinement method. Experimental tests of jointless CFST component and joint component under pure bending condition and compression-bending condition are carried out to obtain the stiffness and strength of different arch sections. Casing joint, which is the most commonly used form of connection joint in CFST arch, shows different mechanical properties with jointless components. Numerical and analytical studies of casing joint are conducted to establish a quantitative design method of joint stiffness. Based on above research results, a mechanical model of CFST arch is proposed in order to construct the SCC for support design. The research results could provide a theoretical basis for the design and application of CFST arch support in related projects.